Pulsed laser removal of tungsten nanoparticle aggregates: Surface analysis and visualization of particle ejection dynamics. (March 2021) - Stokker-Cheregi, F.; Bercea, A.I.; Ojeda-Gonzalez-Posada, A.; Palla-Papavlu, A.; Acsente, T.; Grisolia, C.; Delaporte, P.; Dinescu, G.; Lippert, T.; Dinescu, M.
Highlights: The removal of tungsten layers using ns laser pulses was investigated. Irradiated surfaces were analyzed using SEM, Raman Spectroscopy, XRD and profilometry. The removal of W NPs conglomerates was achieved without damaging the underlying substrate surface. A plasma imaging setup was used to visualize the particle removal process over different time scales. The ejected particle conglomerates had velocities of the order of few hundreds of km/h. Abstract: In this study, we report on some of the aspects that describe the interaction of nanosecond UV laser pulses with solid surfaces covered by layers of tungsten nanoparticles aggregates, with an interest in applications for next-generation fusion reactors. The safe and efficient operation of such reactors is challenged by their unavoidable contamination with dust by-products due to interactions between plasma and the surface of plasma-facing components. We investigate the cleaning possibility of tungsten nanoparticle layers from solid surfaces using a KrF excimer laser source with tailored spot shape. The samples that emulate dust contaminated surfaces are synthesized by magnetron sputtering combined with gas aggregation technique. In order to shed light into the particle removal efficiency, the tungsten samples are investigated by scanning electron microscopy, Raman spectroscopy, and profilometry. Furthermore, in order to gain insight into the W nanoparticles and fragments mobilization dynamics, a plasma imaging setup is used to visualize the speed and directionality of the ejected material. We find that a very good surface cleaning can be achieved, even for the lowest considered laser fluence (0.5 J/cm 2 ) following 8 pulses. Material ejection from the laser irradiated surfaces occurs in two regimes, over very diverse time scales: (i) first, a fast plasma plume travelling at 40, 000 km/h reaches the substrate in a few microseconds, (ii) followed by the ejection of large particle conglomerates at speeds of the order of few hundred km/h. The particle ejection dynamics is shown to differ depending on the type of atmosphere (ambient pressure and vacuum, respectively), whereas the plasma plume evolution could only be evidenced under vacuum conditions.